MELODI PEMBELAJARAN : TANTANGAN DAN KEBERHASILAN SENI BUDAYA DI KELAS 5 SDN CITEREP - Limas, Nida Nabilah; Setiani, Henny; Anggraeni, Aini; Aliansy, Ananda Putri; Nabila, Sakilatun (FKIP Universitas Wisnuwardhana, 2025)
Abstract: This study examines the challenges and successes of learning arts and culture in grade 5 at SDN Citerep. The primary issue addressed is a lack of student interest in arts and cultural items, which are frequently viewed as less fascinating and relevant to their daily life. As a result, students engage in less arts and culture-related learning activities. To address this issue, the author employs an innovative learning method that incorporates visual material such as movies and photos, as well as practical activities that actively engage students in the learning process. This strategy aims to create a joyful and participatory learning environment in which students can better understand and appreciate arts and culture. The adoption of this strategy resulted in a significant rise in student interest and participation during the learning process. The research findings show that an interactive and contextual approach can help pupils grasp arts and culture. Finally, by using creative and fascinating learning approaches, problems in learning arts and culture can be solved, and student interest and understanding can be effectively increased.